Deep sequencing analysis of serum hepatitis B virus‐RNA during nucleot(s)ide analogue therapy. Issue 1 (11th January 2021) - Matsuda, Shuya; Maekawa, Shinya; Komiyama, Yasuyuki; Nakakuki, Natsuko; Muraoka, Masaru; Suzuki, Yuichiro; Sato, Mitsuaki; Tatsumi, Akihisa; Miura, Mika; Amemiya, Fumitake; Shindo, Hiroko; Takano, Shinichi; et al.
Abstract : Aim: Recently, serum hepatitis B virus (HBV)‐RNA has been reported to be detectable even when HBV particle production is inhibited by nucleot(s)ide analogues (NAs). However, the dynamics of the HBV‐RNA sequence compared with those of HBV‐DNA during the emergence of antiviral resistance are yet to be elucidated. Methods: First, we quantified serum HBV‐RNA in 181 infected patients, and its relationships with clinical characteristics as well as HBV markers were investigated. Next, we undertook simultaneous deep sequencing of HBV‐RNA/HBV‐DNA and their dynamics among four patients receiving NA therapy who were experiencing viral breakthrough. Results: Serum HBV‐RNA was detected in 25% (31/123) of cases among patients with HBV without NAs, and the detection rate was significantly high in hepatitis B e antigen‐positive cases with high viral activity. In patients with chronic hepatitis, hepatitis B core‐related antigen was significantly correlated with serum HBV‐RNA irrespective of NA use. In the analysis of the four patients experiencing viral breakthrough, no NA resistance mutation was detected in the serum HBV‐RNA immediately before the breakthrough. However, NA‐resistant sequences appeared at the rates of 0%, 3%, 14%, and 100%, and the NA‐resistant HBV‐RNA sequence rate was correlated with the peak HBV‐DNA titer multiplied by the HBV‐DNA detection duration during the breakthrough (R 2  = 0.978) observed before redisappearance of HBV‐DNA following the addition of new NA. Conclusion: Serum HBV‐RNA could reflect the transcriptional activity of covalently closed circular DNA and hepatitis B core‐related antigen. The dynamics of HBV‐RNA could help understanding of the turnover process of HBV covalently closed circular DNA in the liver.